Analisis Pola Spasial Persebaran Fasilitas Pelayanan Kesehatan Di Kota Pekanbaru - Astuti, Puji; Muffidah, Izatul (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2024)
Health service facilities are needed to provide affordable health services for all levels of society, especially during the pandemic. Based on spatial aspects, existing health facilities in Pekanbaru City cannot be accessed optimally by the people of Pekanbaru City. This research aims to determine the spatial pattern of the distribution of health service facilities in Pekanbaru City. The approach used in this research is quantitative. To determine the distribution pattern of health facilities using nearest neighbor analysis, Geographic Information System (GIS) spatial analysis (buffering) is used to determine the distance of coverage of health facility service areas in Pekanbaru City. The results of the spatial pattern of the distribution of health facilities in Pekanbaru City have a clustered pattern. Based on the results, regarding the distance to hospitals in Pekanbaru City, it is included in the medium category with an area coverage of 36.42% and a distance of more than 1-2 km. The distance to reach the puskesmas services is in the medium and long-distance category with a coverage area of 38.97% with a distance of more than 1 km. The distribution of health facilities does not fully reach the service areas, so additional health facilities are needed for areas that are still not reached.